EFEKTIFITAS PEMBERIAN EKSTRAK DAUN SIRIH (Piper betle. L) TERHADAP PENETASAN TELUR IKAN GURAMI (Osphronemus gouramy. Lac) - Muarofah Ghofur; M. Sugihartono; Riko Thomas (Universitas Batanghari Jambi, 2014)
This study aims to determine the effectiveness of betel leaf extract (P. betle) as an anti-fungal against carp hatchery (O. gouramy) were maintained in a controlled manner inside the aquarium. This research was conducted at the Laboratory of the University of Edinburgh Batang.Eggs test used in this study is gurami roe (O. gouramy) obtained from BBAT River Glam of 1200 eggs with a dense spreading 100 rounds / platform. Containers used in immersion using toples volume of 1 liter of water for 20 minutes, then transferred into an aquarium measuring 30x30x60 cm by 12, filled with water of 20 liters / container and each is equipped with aeration and water heater.Program used was Randomized Lengakap (CRD) with 4 treatments with the provision of betel leaf extract with a concentration of 0 ml, 1.25 ml, 1.50 ml, and 1.75 ml each with three replications. Parameters analyzed are hatching eggs and larvae survival. Results were analyzed with the fingerprint modes, then proceed with further test of Duncan (DNMRT) at the 5% level.From the analysis of variance showed that the difference soaking with betel leaf extract showed a significant influence on the success of hatching eggs and live kelansungan carp larvae (O. gouramy). From the results of research conducted showed that showed that treatment with a concentration of 1.50 ml / l gives results very optimal for egg hatching success was 84.33%, while the survival of larvae was 83.67%.Keyword : effectiveness, betel leaf extract, fish hatchery